Educational psychologists' experiences of supporting intersex children and young people. Issue 2 (3rd April 2021) - Connor, Julie; Atkinson, Cathy
ABSTRACT: While there is increasing awareness of diversity within school-based practice amongst educational psychologists (EPs), one overlooked group is arguably children born intersex, whose needs are often not identified or understood. This research reports an exploratory interview design with a single case to understand the role of an EP in casework undertaken with an intersex young person. Data gathered from a semi-structured interview were analysed using thematic analysis with themes relating to the EP role emerging, under the overarching issue of "acceptance versus denial". This described the conflicting issues of accepting the young person's identity, alongside the need to protect confidentiality, create a safe space and avoid stigma. Recruitment issues suggested that EPs are not identifying working with intersex children, limiting the range and scope of this study. It is hoped that although small scale, this research will encourage further discussion and debate about how EPs can support intersex children and young people (CYP).